DETERMINATION OF MICROBIAL DIVERSITY OF INDIGENOUS MICROFLORA OF SOIL SAMPLES CONTAMINATED WITH XENOBIOTICS AND STUDY OF THEIR MICROBIOLOGICAL PROPERTIES (Eurasian Journal of Ecology, 2025)
The microbial community that determines the biochemical properties of the soil is a set of living organisms of different species that form a certain ecological and trophic unit. Of all the biotic components of the ecosystem, the microbial community is the most sensitive to changes in environmental conditions that occur during agricultural development of ecosystems, as well as to the presence of other forms of anthropogenic impact, including pollutants. The complexity and diversity of the relationships of various microorganisms with each other and with plants, as well as with other components of the agrobiocenosis, determine the phytosanitary state of the soil and its stability as an integral system.The aim of the work is to determine the microbial diversity of the native microflora of soil samples contaminated with xenobiotics and to study their biological properties, as well as screening for promising microorganisms. Study of the microbial diversity of the local microflora of soil samples contaminated with xenobiotics in the Turkestan and Kyzylorda regions.Xenobiotics, getting into the soil, directly or indirectly affect microbial communities. According to modern concepts, microbiological monitoring is a priority area of ​​environmental quality control. Currently, the most developed methods for assessing the impact of pollutants are based on the study of the structural reorganization of communities and the consideration of various groups of microorganisms. In this regard, the work studied the microbial diversity of soils contaminated with xenobiotics in the Turkestan and Kyzylorda regions, and selected promising microorganisms.Keywords: xenobiotics, microorganisms, screening, destructor.